(untitled) (Research, Society and Development, 2020)
The production of pigs on a smaller scale, such as the family, usually uses animals of naturalized breeds, which despite the lower productive performance, are more rustic, adapt to different production systems and present a desirable meat characteristic for the production of products intended for niches market share. The objective of present study was to evaluate whether the reproductive performance of Moura sow is influenced by the genetics of the boar used in mating. The data used were extracted from the zootechnical control sheets of the swine sector of the Unesp Teaching, Research and Extension Farm - Campus of Ilha Solteira - SP, between September 2016 and September 2018. For the evaluation, data from 34 births were validated. of mating of Moura sow with Moura boar (12 deliveries), ½ Moura boar (12 deliveries) and MS115 synthetic boar (10 deliveries). In each delivery, the numbers number of pigs born and pig born alive, rate of stillborn, birth and weaning weight and mortality rate and daily weight gain from birth to weaning were considered. The boar genetics did not interfere (P> 0.05) in any evaluated parameter. Therefore, the use of Moura sow mated with Moura boar, MS115 synthetic boar or ½ Moura boar did not determine differences in litter size, survival and performance until weaning. On average, the number of live births, mortality rate from birth to weaning and daily weight gain were, respectively, 8.82; 12.12% e 0.210 g/day.